Cobra Kai - Season 1 Episode 1-10 - Hurwitz, Jon; Schlossberg, Hayden; Celotta, Jennifer; Duncan, Cameron; Macchio, Ralph; Zabka, William; Maridueña, Xolo (Sony Pictures, 2021)
Set three decades after the plot of "The Karate Kid" (1984), the series follows Johnny Lawrence (Zabka) as he opens the Cobra Kai dojo in an attempt to atone for his past. When his former rival Daniel LaRusso (Macchio) returns, struggling to cope on his own after the death of his mentor, he takes in Johnny's estranged son Robby (Tanner Buchanan) in the hopes of passing on the teachings of his late friend. [www.amazon.co.uk]